ROKAT BHELIONE: MEMAKNAI TRADISI LOCAL WISDOM MASYARAKAT PAMEKASAN SAAT ANGGOTA KELUARGA MENINGGAL DUNIA - Rohman, Mujibur; Haris, Abd; Supandi, Supandi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
Rokat is a tradition of the Madurese people that is still sympathetic and is still being preserved. Rokat is a cultural and religious assimilation that makes researchers interested in exploring it. The research method used is qualitative with a phenomenological type. The data collection methods used were 1) interviews, 2) observation, and 3 documentation analysis, while the research informants were 1) religious leaders, 2) community leaders, and the community. The results of the research show that the implementation of rokat belief in society is as follows: a) rokat belioneh is a salvation activity carried out when a family member dies, b) rokat belioneh is carried out to get closer to Allah SWT, c) rokat belioneh is carried out with several stage (preparation and implementation). Meanwhile, related to the views of the Pamekasan people regarding the rokat bhelioneh tradition when a family member dies, they are: a) rokat bhelioneh is a culture that does not conflict with Islamic teachings. b) Rokat bhelioneh is a tradition carried out to gain approval and mercy from Allah SWT, c) Rokat bhelioneh is carried out to eliminate sadness due to being abandoned by loved ones and aims to obtain the safety of wealth and health from all forms of danger that threatens. The applications of this research activity are 1) the importance of local traditions in dealing with death, 2) the role of family and community in the mourning process, 3) values ​​of belief and spirituality, 4) the maintenance and transmission of traditions and culture.